Perkembangan Tari Setabik di Lingkungan Pendidikan di Sekayu Musi Banyuasin - Rana Arisma Valeves; Indrayuda Indrayuda (Journal on Education, 2024)
Abstract. This article aims to reveal, describe, and analyze the development of Setabik dance in Sekayu Musi Banyuasin district. This type of research is qualitative research with descriptive methods. The object of this research is the Setabik dance in Sekayu district of Musi Banyuasin. The research instrument is the researcher himself as the primary instrument, assisted by other instruments such as observation and interview guidance sheets and visual audio media. Data collection techniques are done by means of library studies, observations, interviews, and documentation. Data analysis is carried out in the following stages: (1) data collection; (2) data reduction; (3) data presentation; (4) data verification and conclusion of data analysis results. The results of the research showed that there were some advances in Setabik dance from the original version, namely the addition of the number of dancers, the variety of dance movements and accessories to the clothes. The Setabik dance, originally called the Tabik Tuan dance, was drawn from the Dutch colonial period in order to welcome the honourable guests and leaders of the Netherlands who came to Musi Banyuasin. Nowadays the dance has been taught to elementary school students up to high school. Besides, the general public who wants to learn Setabik dance lately has no limits. Unlike the conditions of the ancient days, the Setabik dance could only be attracted by the nobility, who initially used to perform only for the reception of guests, but in the development of the dance, the setabik has been presented as a entertainment performance. Thus, in order to preserve the Setabik dance so that it continues, the setabik dancing is a cultural art learning material in the Sekayu district of Musi Banyuasin. Keywords: Setabik dance, Development, and Education Abstrak. Artikel ini bertujuan untuk mengungkapkan, mendeskripsikan, dan menganalisis tentang Perkembangan tari Setabik di Sekayu Kabupaten Musi Banyuasin. Jenis penelitian ini adalah penelitian kualitatif dengan metode deskriptif. Objek penelitian ini adalah tari Setabik di Sekayu Kabupaten Musi Banyuasin. Instrumen penelitian adalah peneliti sendiri sebagai instrumen utama, dibantu dengan instrumen lain yaitu lembar pedoman observasi dan wawancara serta media audio visual. Teknik pengumpulan data dilakukan dengan cara studi kepustakaan, observasi, wawancara, dan dokumentasi. Analisis data dilakukan dengan tahapan sebagai berikut; (1) koleksi data; (2) reduksi data; (3) penyajian data; (4) verifikasi data dan menyimpulkan hasil analisis data. Hasil penelitian menunjukkan bahwa terdapat beberapa perkembangan tari Setabik dari versi awalnya, yaitu penambahan jumlah penari, ragam gerak tari dan aksesoris pada pakaian. Tari Setabik yang pada awalnya bernama tari Tabik Tuan sudah ada dari masa kolonial Belanda yang ditarikan dalam rangka menyambut tamu-tamu kehormatan dan pemimpin Belanda yang datang ke Musi Banyuasin. Pada masa sekarang tari tersebut telah diajarkan pada siswa Sekolah Dasar sampai Sekolah Menengah Atas. Selain itu masyarakat umum yang ingin mempelajari tari Setabik akhir-akhir ini memang tidak ada batasannya. Berbeda dengan kondisi pada zaman dahulu tari Setabik hanya boleh ditarikan oleh kaum bangsawan saja, yang pada awalnya tari Setabik hanya difungsikan untuk penyambutan tamu, tetapi dalam perkembangannya tari Setabik sudah ditampilkan sebagai pertunjukan hiburan. Dengan demikian, guna melestarikan tari Setabik agar terus berkesinambungan, maka tari Setabik menjadi materi pembelajaran seni budaya di Sekayu Kabupaten Musi Banyuasin. Kata Kunci : Tari Setabik, Perkembangan, dan Pendidikan